CYBERSECURITY: THREATS AND SOLUTIONS - Topcu, Neslihan (Cyberpolitik Journal, 2022)
With the spread of information and communication technologies and the birth of the Internet, a new environment called cyberspace has been formed. In 1988, as a result of the Morris worm’s damage to computers and the Internet, it emerged that cyberspace had an insecure side. Thus, the cybersecurity has begun to be addressed in security studies. In this direction, the paper thoroughly examines the question of what cybersecurity is. The paper consists of four parts. In the first part, information society, information security, concepts related to cybersecurity and cybersecurity are explained. Then, under the second part, Myriam Dunn Cavelty and Laura Fichtner’s discourses on cybersecurity are emphasized. In the third part, cybersecurity threats are analyzed. How to take measures against these threats is explained in the fourth section.